Handbook of Oral Anticoagulation - Lip, Gregory YH; Shantsila, Eduard (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
This book covers a wide range of disorders such as atrial fibrillation, artificial heart valves, deep vein thrombosis, pulmonary embolism and stroke. Handbook of Oral Anticoagulation aims to provide an accessible overview of the exciting new developments in this field. Incorporating numerous quick-reference tables and figures and fully referenced throughout to key papers and the latest reviews, it will be a useful resource for all healthcare professionals involved in thromboprophylaxis.